Pengaruh Disiplin Kerja Dan Kinerja Pegawai Terhadap Kualitas Pelayanan Publik Di Dinas Pengendalian Penduduk Keluarga Berencana Pemberdayaan Perempuan Dan Perlindungan Anak Kabupaten Buleleng - Ni Luh Sri Kasih; Gede Hery Prayuda Wijaya (ARTHA SATYA DHARMA, 2022)
The quality of service at government public service institutions is an important concern in realizing the institution's goals. Employee performance becomes the main factor in providing public services and is supported by high work discipline so that the achievement of service targets is achieved. Therefore, the purpose of this study is the influence of work discipline and employee performance on the quality of public services in the Population Control Service, Family Planning, Women's Empowerment and Child Protection, Buleleng Regency. This type of research is quantitative research with the unit of analysis of this research, namely service employees at the Department of Population Control, Family Planning, Women's Empowerment and Child Protection, Buleleng Regency, as many as 37 people. The data analysis technique used is multiple linear regression coefficient analysis, analysis of determination, t-test and F-test, using the computer-assisted program (SPSS) Version 26.00 for Windows. The results of the analysis show that 1) Work Discipline and Employee Performance partially have a positive and significant effect on the Quality of Public Services at the Population Control Service, Family Planning, Women's Empowerment and Child Protection, Buleleng Regency. 2) Work Discipline and Performance have a positive and significant effect simultaneously on the Quality of Public Services. at the Office of Population Control, Family Planning, Women's Empowerment and Child Protection, Buleleng Regency.